A geografia dos contos de Conan Doyle: a Londres de Sherlock Holmes - Pereira Junior, Jair (2020)
Franco Moretti's critical theory contemplates new horizons of perception about literary studies. One of the developments of this proposes that the methodological procedure for analyzing fictional plot maps is configured as a tool that dissects a text in a different way. Thus, the general goal of this study is to build and analyze literary maps of some tales from three anthologies by Arthur Conan Doyle, namely: The adventures of Sherlock Holmes, The memories and The return, in order to show, to a large extent, the category of fictional spaces in Doyle, where the streets, neighborhoods and regions of Sherlock Holmes’ London appear in intersection, intersection, exclusivity or exclusion in the different detective narratives. The undertaking of this study also makes use of the concepts and definitions related to the police short-story genre by Edgar Allan Poe and who is also characterized as the precursor and influential of this subgenre. In addition, this research provides a review of the conceptualization of the short-story genre, highlighting the Poe’s, Júlio Cortázar‘s, Brander Matthews‘ and Horácio Quiroga’s theoretical propositions. The results of the research show that the dialogue, therefore, between literature and geography, in the Morettian perspective, makes clear the relationships called hidden in the materialization of maps, which are in the power of analysis through textual elements.